Editor’s Foreword - Radaev, Vadim (Journal of Economic Sociology, 2021)
Dear colleagues, This new issue of our journal comes out during these difficult times. The second wave of the COVID-19 pandemic is on its way. It brings new challenges, which are comparable with those of the previous wave. Lockdowns and distant communications are returning. We hope that you and your friends and relatives will survive this time safely.